1991
DOI: 10.1111/j.1540-6261.1991.tb02673.x
|View full text |Cite
|
Sign up to set email alerts
|

Financial Investment Opportunities and the Macroeconomy

Abstract: This paper studies the relation between changes in financial investment opportunities and changes in the macroeconomy. States variables such as the lagged production growth rate, the default premium, the term premium, the short‐term interest rate and the market dividend‐price ratio are shown to be indicators of recent and future economic growth. Further, the market excess return is negatively correlated with recent economic growth and positively correlated with expected future economic growth. These results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
138
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(153 citation statements)
references
References 41 publications
10
138
0
2
Order By: Relevance
“…Second, regarding predictability, it is found that the lagged maturity premium is related with the equity premium only in the low volatility regime, thereby indicating regime-dependent predictability of the equity premium. Importantly, the predictability relation is positive, in line with previous evidence for the USA (Campbell 1987;Fama and French 1989;Chen 1991). This result is robust to an alternative definition of the equity risk premium in terms of the long term government yield (instead of the Treasury bill yield), and to the inclusion of the real interest rate and the real growth rate in the regime switching VAR as control variables.…”
supporting
confidence: 86%
“…Second, regarding predictability, it is found that the lagged maturity premium is related with the equity premium only in the low volatility regime, thereby indicating regime-dependent predictability of the equity premium. Importantly, the predictability relation is positive, in line with previous evidence for the USA (Campbell 1987;Fama and French 1989;Chen 1991). This result is robust to an alternative definition of the equity risk premium in terms of the long term government yield (instead of the Treasury bill yield), and to the inclusion of the real interest rate and the real growth rate in the regime switching VAR as control variables.…”
supporting
confidence: 86%
“…Consistent with the arbitrage pricing theory, increases in the market returns are expected to lead to increases in individual stock returns (see for example, Chen, 1991;Chen et al, 1986). Previous business cycle research has highlighted the importance of interest rates in explaining stock price movements (see for example, Chen, 1991;Chen et al, 1986).…”
Section: Empirical Methodologymentioning
confidence: 84%
“…Previous business cycle research has highlighted the importance of interest rates in explaining stock price movements (see for example, Chen, 1991;Chen et al, 1986). Positive term spreads are generally observed during periods of economic expansion and negative term spreads, which correspond to an inverted yield curve, are observed prior to periods of economic contraction.…”
Section: Empirical Methodologymentioning
confidence: 98%
“…Nevertheless, recent advances in asset pricing theory seem to demonstrate that a certain degree of timevarying expected returns is necessary to reward investors for bearing certain dynamic risks associated with the business cycle. Loosely, it is claimed that the equity premium rises during an economic slow-down and falls during periods of economic growth, so that expected returns and business conditions move in opposite directions [see, e.g., FAMA and FRENCH (1989), CHEN (1991), FAMA (1991), andHARVEY (1991)]. However, certain aspects of the empirical research on stock market predictability remain controversial.…”
Section: Introductionmentioning
confidence: 97%